Low temperature solution synthesis of ZnSb, MnSb, and Sr-Ru-O compounds - Noblitt, Jennifer Lenkner, author; Prieto, Amy L., advisor; Dandy, David S., committee member; Elliott, C. Michael, committee member; Fisher, Ellen R., committee member; Van Orden, Alan K., committee member (Colorado State University. Libraries, 2011)
Increasing energy demands are fueling research in the area of renewable energy and energy storage. In particular, Li-ion batteries and superconducting wires are attractive choices for energy storage. Improving safety, simplifying manufacturing processes, and advancing technology to increase energy storage capacity is necessary to compete with current marketed energy storage devices. These advancements are accomplished through the study of new materials and new morphologies. Increasing dependence on and rising demand for portable electronic devices has continued to drive research in the area of Li-ion batteries. In order to compete with existing batteries and be applicable to future energy needs such as powering hybrid vehicles, the drawbacks of Li-ion batteries must be addressed including (i) low power density, (ii) safety, and (iii) high manufacturing costs. These drawbacks can be addressed through new materials and morphologies for the anode, cathode, and electrolyte. New intermetallic anode materials such as ZnSb, MnSb, and Mn2Sb are attractive candidates to replace graphite, the current industry standard anode material, because they are safer while maintaining comparable theoretical capacity. Electrodeposition is an inexpensive method that could be used for the synthesis of these electrode materials. Direct electrodeposition allows for excellent electrical contact to the current collector without the use of a binder. To successfully electrodeposit zinc and manganese antimonides, metal precursors with excellent solubility in water were needed. To promote solubility, particularly for the antimony precursor, coordinating ligands were added to the deposition bath solutions. This work shows that the choice of coordinating ligand and metal-ligand speciation can alter both the electrochemistry and the film composition. This work focuses on the search for appropriate coordinating ligands, solution pH, and bath temperatures so that high quality films of ZnSb, MnSb, and Mn2Sb may be electrochemically deposited on a conducting substrate. Increasing use of natural resources for energy generation has driven research in the area of energy storage using superconducting materials. To meet energy storage needs the materials must have the following features: (i) safety, (ii) superconductivity at or above liquid nitrogen temperature (77 K), (iii) low cost manufacturing processes, and (iv) robustness. The search for materials that meet all of these criteria is on-going, specifically in the area of high temperature superconductivity. The precise mechanism of superconductivity is not known. A few theories explain some of the phenomenological aspects, but not all. In order to logically select and synthesize high temperature superconductors for industrial applications, the precise mechanism must first be elucidated. Additionally, a synthetic method that yields pure, high quality crystals is required because transition temperatures have been shown to vary depending on the preparation method due to impurities. Before measuring properties of superconductors, the development of a synthesis method that yields pure, high quality crystals is required. Most superconductors are synthesized using traditional solid state methods. This synthesis route precludes formation of kinetically stable phases. Low temperature synthesis is useful for probing thermodynamic verses kinetic stability of compounds as well as producing high quality single crystals. A novel low temperature hydrothermal synthesis of Sr-Ru-O compounds has been developed. These materials are important because of their interesting properties including superconductivity and ferromagnetism. Sr2RuO4 is particularly interesting as it is superconducting and isostructural to La2CuO4, which is only superconducting when doped. Therefore, Sr2RuO4 is a good choice for study of the mechanism of superconductivity. Additionally, new kinetically stable phases of the Sr-Ru-O family may be formed which may also be superconducting. Sr-Ru-O compounds were previously synthesized via the float zone method. There is one report of using hydrothermal synthesis, but the temperatures used were 480-630 °C. In general, hydrothermal methods are advantageous because of the potential for moderate temperatures and pressures to be used. Additionally, the reaction temperature, precursor choice, and reaction time can all be used to tune the composition and morphology of the product. Hydrothermal methods are inexpensive and a one-step synthesis which is very convenient to scale up for industrial application. This work shows how a hydrothermal method at temperatures between 140 °C and 210 °C was developed for the synthesis of the Sr-Ru-O family of compounds.
Keywords: hydrothermal; zinc antimonide; strontium ruthenate; intermetallic; manganese antimonide; electrodeposition